PELESTARIAN BAHAN PUSTAKA DI PERPUSTAKAAN IAIN PONTIANAK - Hafiz, Aslam; Latifa Hanum, Atiqa Nur (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis research is based on the researcher's desire to know the preservation of library collections in IAIN library Pontianak. The purpose of this final project is to explain the cause of the damage of library materials on doing the preservation in IAIN library Pontianak. In this research, the researcher conducted the research using descriptive method in the form of qualitative approach. The technique of data collection was done through observation, interview and documentation which was done by the researcher to the informans such as the head of the library, the processor staff and circulation service. The finding of this research showed that the preservation of library materials in IAIN library Pontianak has not optimal yet. There were many library collections that had been damaged but still used by the librarians. The factors which damaged the library materials were caused by the insects and humans. In doing the prevention, the librarians still used the simple tools such as binding and gluing the materials. The librarians never do any of the prevention like fumingation, lamination and deasidification. The obstacles faced by the librarians were such as: there was no special guidelines for preservation, lack of facilities, staff and fund.Keywords: Preservation, library collections